Efficacy of salbutamol and ipratropium bromide in the management of acute bronchiolitis - A clinical trial - KARADAĞ, BÜLENT TANER (KARGER, 2008)
Background: A wide range of drugs are commonly used to treat bronchiolitis, but evidence of their effectiveness is limited. Objectives: To investigate the efficacy of ipratropium bromide and salbutamol in the treatment of patients with moderate-severe bronchiolitis. Methods: Sixty-nine infants with moderate- severe bronchiolitis hospitalized at their first episode of wheezing or crepitations in the chest were enrolled in a prospective, double-blind, placebo-controlled trial. Patients were randomly assigned to receive nebulized salbutamol, ipratropium bromide or placebo. Main outcome measures were changes in oxygen saturation rates and clinical scores and duration of hospitalization. Results: In the bronchodilator groups, clinical scores were better compared to the placebo group at 30 min ( 8.4 +/- 1.3 vs. 7.5 +/- 0.8, p < 0.05). Bronchodilator groups had also significantly lower clinical scores (7.3 +/- 1.2 vs. 5.9 +/- 1.1, p < 0.0001, and 5.3 +/- 1.4 vs. 4.5 +/- 1.6, p = 0.006, respectively) and higher oxygen saturation rates compared to the placebo group at 8 and 24 h ( 89.6 +/- 2.4 vs. 94.3 +/- 4.4, and 92.2 +/- 2.6 vs. 95.9 +/- 4.4, respectively, p < 0.0001). Improvement rates and duration of hospitalization were not statistically different among groups. Conclusions: Clinical scores and oxygen saturation levels improved more rapidly in the bronchodilator groups than in the placebo group up to 24 h, but these drugs did not have a sufficient effect to change the natural course of the disease. Copyright (C) 2007 S. Karger AG, Basel.
Keywords: bronchiolitis; bronchodilators; children; ipratropium bromide; salbutamol; BRONCHODILATORS; THERAPY; INFANTS